Value-added Agriculture, Investment, and Infrastructure Development in the Indonesian Economy: VECM Approach - Budi Sasongko; Sri Harnani; Suryaning Bawono (Asia Pacific Journal of Management and Education (APJME), 2022)
The purpose of this study was to determine the impact of the relationship between agricultural value-added on investment and infrastructure development in Indonesia. This study uses data from a period of 36 years, from 1985 to 2020, with vector modeling to understand the causal relationship between variables. This research is based on secondary data from the world bank. We use the variables of value-added agriculture, investment, and infrastructure in Indonesia. The findings of this study indicate that macroeconomic factors such as value-added agriculture, non-financial investment, and infrastructure (percentage of government spending) are all interrelated. Changes in one variable will have an impact on other variables. As the value of agriculture declines, the Indonesian government will boost infrastructure spending. This happens because the decline in the value-added of agriculture in Indonesia can hamper infrastructure growth because the existing infrastructure is considered sufficient to support the needs of the agricultural sector. Increased investment, on the other hand, will increase the value-added of agriculture, which implies that agriculture is still receiving a sizeable investment and will continue to play a significant role in non-financial investment.